If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 6x + 6x = 69 Combine like terms: 6x + 6x = 12x 9 + 12x = 69 Solving 9 + 12x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 12x = 69 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = 69 + -9 12x = 69 + -9 Combine like terms: 69 + -9 = 60 12x = 60 Divide each side by '12'. x = 5 Simplifying x = 5
| 3x+1+3x=25 | | 0.5-2.5n=1-1.3n | | 10+7x=31 | | x+0.06x=1600 | | 7x+24=5 | | 136.27+23.5W=253.77 | | 4y+7=1y+3 | | v-33=v-6 | | 10x-21=15-2x | | 2+6x=50 | | x+(x*4)=75 | | (X-4)(x-3)=0 | | -6x-11=-49 | | 9=7x-2(x-4) | | 3m+15=28m | | 8X+7=22+3X | | 3Z+16=25 | | 3a+8+2a=a-9+1 | | 1-9n=80 | | 0.5x(x-4)=0 | | 10x^2-11x-8=0 | | 12.4=4.7+X | | 11x-18+6x+12=360 | | -4+6=-42 | | 12n*4n= | | 3z^2+z-2=0 | | 3a^2-4a-2=0 | | z^3-1=0 | | H(x)=4x^4-5x^3+2x^2-x+5 | | 4v+5(1-3v)=-17 | | 4w+3w=-28 | | 15d+1=8d+8 |